Penjual Pisang Nugget - Rahayu, Cici; Ashmarita, Ashmarita (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2025)
This research aims to examine and describe how service is provided to consumers and how social responsibility is carried out by Banana Kob's in Kendari City. Selection of informants in this study using a purposive technique. This study uses the theory of Social Organization Caroll Stack. The data collection techniques used in this research are participant observation techniques and in-depth interviews. This research is a qualitative research using ethnographic research methods. The results of this research show that: first, it shows that the service to consumers at Banana Kob's is consumer satisfaction with the contemporary culinary business, namely banana nuggets and good communication relationships between business owners, employees and consumers. This will affect the quality of service at the Banana Kob's Outlet. Second, the corporate social responsibility of the banana nugget seller at the Banana Kob's outlet in Kendari City, even though it is a UMKM, still provides social responsibility to employees and the community in the form of balance between work and employees' personal lives, namely by arranging work hours or changing shifts, as well as providing work holidays two or three times a month, and providing salaries in accordance with the agreement. Then give a holiday to employees, namely holding a company birthday celebration by scheduling a joint holiday for all employees so they can celebrate Banana Kob's birthday. Apart from that, Banana Kob's also carries out charity activities, namely by distributing takjil in the month of Ramadan and donating food. Social responsibility activities were carried out unknowingly by the UMKM owner selling banana nuggets at the Banana Kob's outlet in Kendari City